2015
DOI: 10.1016/j.vaccine.2015.06.101
|View full text |Cite
|
Sign up to set email alerts
|

The weight of obesity on the human immune response to vaccination

Abstract: Despite the high success of protection against several infectious diseases through effective vaccines, some sub-populations have been observed to respond poorly to vaccines, putting them at increased risk for vaccine-preventable diseases. In particular, the limited data concerning the effect of obesity on vaccine immunogenicity and efficacy suggests that obesity is a factor that increases the likelihood of a poor vaccine-induced immune response. Obesity occurs through the deposition of excess lipids into adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 85 publications
4
132
3
2
Order By: Relevance
“…Literature identifies medications such as risperidone, epinephrine, Depo-Provera, human chorionic gonadotropin (hCG), and Hepatitis A and B, rabies, and tetanus vaccines that if given into the subcutaneous tissue do not reach therapeutic effectiveness. [1][2][3] Instructions for IM injection technique vary in literature and in nursing texts, including guidelines for weight and gender, injection site, needle gauge and length, bunching or stretching the skin, aspiration, and z-track method. [4,5] As an example, educational texts offer inconsistencies in IM injection practices pertaining to z-track technique.…”
Section: Practice Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature identifies medications such as risperidone, epinephrine, Depo-Provera, human chorionic gonadotropin (hCG), and Hepatitis A and B, rabies, and tetanus vaccines that if given into the subcutaneous tissue do not reach therapeutic effectiveness. [1][2][3] Instructions for IM injection technique vary in literature and in nursing texts, including guidelines for weight and gender, injection site, needle gauge and length, bunching or stretching the skin, aspiration, and z-track method. [4,5] As an example, educational texts offer inconsistencies in IM injection practices pertaining to z-track technique.…”
Section: Practice Variationmentioning
confidence: 99%
“…Current evidence guides practice to consider gender when administering an IM injection. [2,3,[11][12][13] Recent evidence recommends ventrogluteal site be the preferred site for IM injections. [14,15] Evidence shows the ventrogluteal site is far from major vascular and nerve structures and has a relatively low subcutaneous thickness in comparison with the traditionally used dorsogluteal site.…”
Section: Practice Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Additionally, more and more evidences have suggested that obese individuals had lower rate of antibody responses to vaccines, as compared with those non-obese subjects. 9,10 In the present commentary, we discussed the potential influences of obesity on the immunogenicity of hepatitis B vaccines.…”
Section: Introductionmentioning
confidence: 99%